The grasshopper genome reveals long-term gene content conservation of the X Chromosome and temporal variation in X Chromosome evolution - Li, Xinghua; Mank, Judith E.; Ban, Liping (Genome Research, 2024)
We present the first chromosome-level genome assembly of the grasshopper, Locusta migratoria, one of the largest insect genomes. We use coverage differences between females (XX) and males (X0) to identify the X Chromosome gene content, and find that the X Chromosome shows both complete dosage compensation in somatic tissues and an underrepresentation of testis-expressed genes. X-linked gene content from L. migratoria is highly conserved across seven insect orders, namely Orthoptera, Odonata, Phasmatodea, Hemiptera, Neuroptera, Coleoptera, and Diptera, and the 800 Mb grasshopper X Chromosome is homologous to the fly ancestral X Chromosome despite 400 million years of divergence, suggesting either repeated origin of sex chromosomes with highly similar gene content, or long-term conservation of the X Chromosome. We use this broad conservation of the X Chromosome to test for temporal dynamics to Fast-X evolution, and find evidence of a recent burst evolution for new X-linked genes in contrast to slow evolution of X-conserved genes.